Peran Guru Kelas dalam Implementasi Nilai-nilai Multikultural dalam Pembelajaran Aqidah Akhlak pada Siswa Kelas V di MI Integral Hidayatullah - Hamid Zulfikar Renfaan; A. Arif Rofiki; A. Ubaidillah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the role of class teachers in the implementation of multicultural values ​​in the learning of faith and morals to fifth grade students at MI Integral Hidayatullah Holtekamp and describe the variety of multicultural values ​​that exist in the MI Integral Hidayatullah environment. This type of research is qualitative. The research subjects were the Principal, Class Teachers, and three fifth grade students. The data collection methods used were observation, interviews, and documentation. Data analysis was carried out by means of data collection, data reduction, data presentation, and data verification. Data validation used the triangulation method of data sources. The role of class teachers in the implementation of multicultural values ​​in the learning of faith and morals to students at MI Integral Hidayatullah Holtekamp includes: a. Class teacher motivators become encouragement and role models so that students remain diligent and respect differences. b. Class teacher facilitators act as the main intermediaries in the process of changing student behavior, and c. Class teacher evaluators evaluate attitudes by observing student behavior. The variety of multicultural values ​​at MI Integral Hidaytullah: a. Inclusive: Classroom teachers play a role in creating learning that respects diversity. b. Prioritizing Dialogue: Classroom teachers encourage students to discuss. c. Humanistic: Classroom teachers prioritize a humanitarian attitude in educating students.